2007
DOI: 10.1007/s10509-007-9496-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for monochromatic unstable Weibel modes in asymmetric counterstreaming pair plasmas

Abstract: In this article, an asymmetric counterstreaming distribution function is investigated on the basis of threedimensional relativistic particle-in-cell simulations for wave propagation at an oblique angle with respect to the axis of the counterstream. For such asymmetric distribution functions, any linear Weibel modes must be isolated and therefore restricted to discrete wavenumber values. Using analytical linear Vlasov theory, this result has recently been proven generally, and has been illustrated by the exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…General results on the filamentation instability have thus been obtained by Tzoufras et al 128 in the case of separable nonrelativistic distributions. Likewise, the Weibel instability has been investigated by Tautz et al, [129][130][131][132] who found that the unstable k spectrum may be discrete instead of continuous under certain conditions.…”
Section: -6mentioning
confidence: 99%
“…General results on the filamentation instability have thus been obtained by Tzoufras et al 128 in the case of separable nonrelativistic distributions. Likewise, the Weibel instability has been investigated by Tautz et al, [129][130][131][132] who found that the unstable k spectrum may be discrete instead of continuous under certain conditions.…”
Section: -6mentioning
confidence: 99%
“…Instabilities of relativistic pair plasma beams have been already studied using kinetic plasma simulations (Silva et al 2003;Tautz et al 2007;Cottrill et al 2008;López et al 2014;Lòpez et al 2015;D'Angelo et al 2015;Shukla et al 2015). Only a few studies, however, have assumed relativistic covariant Maxwell-Jüttner distributions, and if so, they were mostly considered to be three-dimensional (Bret et al 2008(Bret et al , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…It is then followed by a significant decrease and shift into a left‐handed polarized mode, where the shifting point in ℜ(ω) = 0 corresponds to the purely growing Weibel instability, ℑ(ω) > 0. This shifting point, however, corresponds to an isolated Weibel mode (Tautz et al 2006; Tautz & Lerche 2007a; Tautz, Sakai & Lerche 2007), because only at one single wavenumber is there an aperiodic Weibel mode. All neighbouring waves do have a real frequency part, however small, and thus propagate away with time.…”
Section: Numerical Solutionsmentioning
confidence: 99%